"Ödmjuk design": Kulturanalytikern som medskapare i teknisk produktutveckling - Bhatt, Robert (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2006)
In this article I talk about the experience of contributing as an ethnologist in the multidisciplinary development of a technical aid for people suffering from dementia. From the viewpoint of a near graduate of the Cultural Analysis Programme in Umeå I discuss some theoretical and practical problems that one inevitably come to face as a scholar in this field wanting to produce concrete, recognisable artefacts for groups outside the academic society. As an example I address the problem of tailoring together methods to suit the heterogeneous needs of project members from different fields such as computer scientists and medical experts without giving up the professional integrity sustained in ethnographic work conducted under "normal" conditions. For this purpose I explain my inspiration by methods common in other fields such as focus groups and the use of video documentation. I also try to frame the project and my participation in it from a critical standpoint. Objection could be made for instance about the way our cooperative efforts set experts knowledge above the reasoning of potential users and reproduce physiological discourses about dementia.